2020
DOI: 10.1177/0271678x20935171
|View full text |Cite
|
Sign up to set email alerts
|

Regional hyperperfusion in older adults with objectively-defined subtle cognitive decline

Abstract: Although cerebral blood flow (CBF) alterations are associated with Alzheimer’s disease (AD), CBF patterns across prodromal stages of AD remain unclear. Therefore, we investigated patterns of regional CBF in 162 Alzheimer’s Disease Neuroimaging Initiative participants characterized as cognitively unimpaired (CU; n = 80), objectively-defined subtle cognitive decline (Obj-SCD; n = 31), or mild cognitive impairment (MCI; n = 51). Arterial spin labeling MRI quantified regional CBF in a priori regions of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 52 publications
9
50
0
Order By: Relevance
“…A 10-year longitudinal study based on the AD Neuroimaging Initiative showed that individuals with Obj-SCD progressed to MCI 2.5-3.4 times faster than the normal group (Thomas et al, 2018). An arterial spin labeling MRI study reported that compared with the normal cognitive function group, the cerebral blood flow of the Obj-SCD participants increased in the hippocampus and inferior parietal; compared with the MCI group, the cerebral blood flow increased in the hippocampus, inferior parietal, and inferior temporal (Thomas et al, 2021). A longitudinal study for 4 years found that Obj-SCD amyloid protein accumulated faster and showed faster thinning of the internal olfactory cortex than the normal group (Thomas et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A 10-year longitudinal study based on the AD Neuroimaging Initiative showed that individuals with Obj-SCD progressed to MCI 2.5-3.4 times faster than the normal group (Thomas et al, 2018). An arterial spin labeling MRI study reported that compared with the normal cognitive function group, the cerebral blood flow of the Obj-SCD participants increased in the hippocampus and inferior parietal; compared with the MCI group, the cerebral blood flow increased in the hippocampus, inferior parietal, and inferior temporal (Thomas et al, 2021). A longitudinal study for 4 years found that Obj-SCD amyloid protein accumulated faster and showed faster thinning of the internal olfactory cortex than the normal group (Thomas et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We examined the following five a priori ROIs: (1) medial temporal lobe (MTL), which included the hippocampus and entorhinal cortex, (2) precuneus, (3) inferior parietal lobe (IPL), ( 4) medial orbitofrontal cortex (mOFC), and (5) pericalcarine cortex. The first four ROIs were chosen given prior work showing these regions are vulnerable to early AD-related changes and have associations between CBF and AD severity (Bangen et al, 2017;Dickerson et al, 2011;Mattsson et al, 2014;Thomas et al, 2021;Yew & Nation, 2017). The pericalcarine ROI was selected as a control region to examine specificity of any results given that there are no expected changes in AD (Mattsson et al, 2014;Sanchez et al, 2020).…”
Section: Structural and Arterial Spin Labeling Mrimentioning
confidence: 99%
“…The pericalcarine ROI was selected as a control region to examine specificity of any results given that there are no expected changes in AD (Mattsson et al, 2014;Sanchez et al, 2020). Consistent with other CBF work in ADNI (Mattsson et al, 2014;Thomas et al, 2021;Yew & Nation, 2017), CBF of the precentral gyrus was selected to serve as a covariate in the models, as it is not thought to be impacted in early AD, allowing for adjustment of expected individual differences in CBF that are likely not due to AD pathologies. If participants were missing baseline ASL data but had ASL data within the first year of their baseline visit, the first occasion of ASL data was used in our analyses.…”
Section: Structural and Arterial Spin Labeling Mrimentioning
confidence: 99%
See 2 more Smart Citations